How to achieve circular economy with systemic change in textile ecosystem - Kuosmanen, Susanna (My University, 2021)
Circular economy is a common topic in the academic research, contributing to the transformation from linear economy to circular economy. Systemic change approach is needed to make actors collaborate and create a global, unified transformation where all the stakeholders, policies, companies, societies, and consumers are working for the same goal. The aim of this study is to investigate how systemic change can contribute to circular economy in the business ecosystem. There are three sub questions, asking how does systemic change support the transition towards a circular economy, what are the main factors to enable systemic change in the ecosystem and what are the main challenges for implementing systemic change in the ecosystem. The study was done by first defining the terms circular economy and systemic change and explaining why systemic change is required to create a unified overview of the subject. Strategies to achieve systemic change in circular economy are explained. Later circular ecosystem is explained and how circularity is adopted in the ecosystem with systemic change. Finally, in the empirical chapters eight case interviews are analyzed and in discussions are connected to the circular ecosystem theory using the framework composed from literature. Main results underline that case companies named consumers, legislation, and the development and further use of recycled materials as the main challenges and changes needed when achieving circular ecosystem. The lack of consumer interest and knowledge undermines the actions by the actors in the ecosystem. Legislation creates the playground for the actors to be in, and if the rules are not united the game is not fair. Recycled materials create the circular loop and brings the materials from linear to circular business. Technology, standardizing, materials, design, financing, and other aspects affect to each other, and systemic change is required to keep all the parts from the chain and ecosystem in cooperation. Results of this research support the theory and previous studies, with the fact that systemic change acts as the main contributor for the circular economy. Most of the issues regarding circular economy require cooperation and collaborated actions by the actors in the ecosystem and cannot contributed by the actors alone. Circular ecosystem combines environmental benefits to economic growth. It offers a profitable opportunity to replace linear production model and systemic change plays a significant role achieving circular ecosystem. Results can be exploited in other industries.

Kiertotalous on akateemisessa tutkimuksessa ajankohtainen aihe, ja tutkimukset esittävät muutoksen lineaarisesta taloudesta kiertotalouteen. Tarvitaan systeemistä muutosta, jotta toimijat voivat tehdä yhteistyötä ja luoda maailmanlaajuisen, yhtenäisen muutoksen, jossa kaikki sidosryhmät, poliitikot, yritykset, yhteiskunnat ja kuluttajat toimivat samaa tavoitetta kohti. Tämän tutkimuksen tavoitteena on selvittää systeemistä muutosta ja sitä, miten sillä voidaan edistää kiertotaloutta ekosysteemissä. Tutkimuksessa on kolme alakysymystä, jotka selvittävät miten systeeminen muutos tukee siirtymää kohti kiertotaloutta, mitkä ovat tärkeimmät tekijät mahdollistamaan systeeminen muutos ekosysteemissä ja mitkä ovat tärkeimmät haasteet systeemisen muutoksen toteuttamiselle ekosysteemissä. Tutkimus tehdään ensin määrittelemällä termit kiertotalous ja systeeminen muutos ja selittämällä, miksi tarvitaan systeemistä muutosta, jotta aiheelle saadaan yhtenäinen yleiskatsaus. Strategiat kiertotalouden systeemisen muutoksen aikaansaamiseksi esitellään. Kiertotalouden ekosysteemi kuvataan ja miten kiertotalous omaksutaan ekosysteemissä. Lopuksi empiirisissä luvuissa haastattelut analysoidaan ja liitetään kiertotalouden ekosysteemiteoriaan. Päätuloksissa tutkimuksen kohteet nimesivät kuluttajat, lainsäädännön sekä kierrätysmateriaalien kehittämisen ja jatkokäytön keskeisiksi haasteiksi ja muutoksiksi, joita tarvitaan kiertotalouden ekosysteemin saavuttamisessa. Kuluttajien kiinnostuksen ja tietämyksen puute heikentää ekosysteemin toimivuutta. Lainsäädäntö luo kentän toimijoille, ja jos säännöt eivät ole yhtenäisiä ne eivät kannusta kiertotaloustoimiin. Kierrätysmateriaalit toteuttavat siirron lineaarisesta liiketoimintamallista kiertotalousmalliin. Teknologia, standardointi, materiaalit, suunnittelu ja rahoitus vaikuttavat toisiinsa. Lisäksi tarvitaan systeemistä muutosta, jotta kaikki osat ekosysteemistä tekisivät yhteistyötä. Tutkimuksen tulokset tukevat teoriaa ja aikaisempia tutkimuksia esimerkiksi esittämällä, että systeeminen muutos vaikuttaa kiertotalouden toteuttamiseen. Suurin osa kiertotalouteen liittyvistä kysymyksistä edellyttää ekosysteemin toimijoiden yhteistyötä ja yhteistyötoimia, johon systeeminen muutos vaikuttaa. Kiertotalous soveltuu liiketoimintamalliksi yhdistäen ympäristöhyödyt ja talouskasvun. Systeemisellä muutoksella ekosysteemissä saadaan aikaan johdonmukainen muutos.
Keywords: systemic change, circular economy, circular business ecosystem, textile industry, systeeminen muutos, kiertotalous, ekosysteemi, tekstiiliteollisuus